Support in providing adequate nutrition for the length of treatment for patients after bone fracture surgery at the Meuraxa Hospital, Banda Aceh - T. Alamsyah; Marniati Marniati; Niswah Niswah; Nurhayati Nurhayati; Fajriansyah Fajriansyah; Ritawati Ritawati (AcTion: Aceh Nutrition Journal, 2023)
One of the problems in fulfilling nutrition is the knowledge or belief that consuming excess protein will result in a longer wound-healing process. Meanwhile, nutritional status is essential in fulfilling nutrients for wound healing and length of stay in postoperative fracture clients. The study aims to determine the relationship between the fulfilment of nutritional needs in participants after lower extremity fracture surgery at Meuraxa Hospital, Banda Aceh City. This research design method is correlation analysis with a cross-sectional approach with a non-probability sample technique with a sample of 83 post-surgical bone fracture patients. The calculation method uses the formula for a 10% error rate from the total population of post-fracture inpatients 123 respondents. The research location is Meuraxa Hospital, Banda Aceh, and it was conducted in March 2021. Results, there is a relationship between knowledge about nutritional fulfilment (p= 0,005), eating habits (p= 0,002), and perceptions of dietary restrictions (p= 0,002) with the length of treatment days in patients after bone fracture surgery at Meuraxa Hospital Banda Aceh. In conclusion, nutrition support affects the length of treatment days, where knowledge, habits and abstinence can shorten treatment days.